Establishment of Thermal Ductile Fracture Criterion for As-Cast 42CrMo Steel and Its Application in Hot Ring Rolling Process - Yuanyuan Chen; Huiping Qi; Yongtang Li; Lin Hua (Advances in Materials Science and Engineering)
The casting-rolling compound forming process of ring parts is an advanced plastic forming technology that has been developed due to the merits of high efficiency and energy and material saving. However, cracks often occur during the hot ring rolling process, especially at the edges of the ring parts, which severely affects the forming quality. To predict and try to avoid the occurrence of cracks in the casting-rolling compound forming process of ring parts, the high-temperature fracture behaviors of as-cast 42CrMo steel were investigated by thermodynamic experiment method. The high-temperature tensile tests were carried out using the Gleeble-3500D thermomechanical simulator at various temperatures and strain rates. Stress-strain curves and fracture morphology were examined, through which the sensitivity of stress to temperature and strain rate and the effect of dynamic recrystallization and cavity evolution on fracture were found. The law of critical fracture strains was analyzed, and the model of critical fracture strain as a function of temperature and strain rate was established. Based on Oyane criterion, the thermal ductile fracture criterion was established in conjunction with the model of critical fracture strain. By embedding this thermal damage model into the finite element (FE) model for hot ring rolling of an as-cast 42CrMo ring, the damage prediction for this process was realized, and the thermal ductile fracture criterion was proved to be reliable. From the FE results for hot ring rolling, mechanism of damage and fracture in the hot ring rolling process was analyzed. The damage threshold Cf is small, and the damage ratio D is large at the top and bottom edges of the inner surface area of the ring, which have the greatest propensity to cracking in the course of hot ring rolling. This is of great significance in terms of improving the forming quality of ring parts in the casting-rolling compound forming process.